The psychiatric treatment of 'behavioural problems' in adolescence: Between coercion and socialisation. Issue 3 (1st September 2016) - Coutant, Isabelle
ABSTRACT: A 2005 report from the French Institute for Medical Research highlighted factors likely to prompt 'behavioural problems' in children and adolescents, and recommended early identification of at-risk families. A number of mental health professionals rose up against such medicalisation of social issues. This ethnographic study was conducted in this climate, in a psychiatric unit, located in a disadvantaged area in the outskirts of Paris, that specialises in adolescents with such problems. The research emphasised how professionals resist being instrumentalised by juvenile counselling services and the justice system, the observed practices bearing traces of critiques of psychiatric institutions since the 1960s. Psychiatrists thus try to justify and legitimate their interventions, which are co-constructed by relevant counselling and mental health professionals and, as much as possible, adolescents and their parents. Consequently, full understanding of institutionalisation, beyond its aspects of constraint and subjection, also requires consideration of its potential as a step in the socialisation process, especially for adolescents from working class backgrounds bereft of social and cultural capital. Contact with professionals may confer a kind of power, 'the power to speak'. At least, that is what the professionals try to give them using the 'pedagogy of reflexivity'.